2011
DOI: 10.4317/medoral.16.e330
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of androgen receptor in carcinoma arising in pleomorphic salivary adenoma

Abstract: Summary: Carcinoma originating within a pre-existing in pleomorphic adenoma is well-known phenomena and is occasionally debated in the field of surgical pathology. The use of the hormone treatment in salivary gland cancers is controversial. The management of patients who show positive reactivity to androgen receptor in prostate carcinomas has guided the researchers to assess the expression of this receptor in a variety of other tumors, including those arising in the salivary glands and particularly in carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Androgen receptor was described in the context of SGC in up to 50% of the cases, and most originated in the parotid gland (Tarakji & Kujan 2011; Nasser et al 2003). Its prevalence was distributed evenly between genders (Nasser et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Androgen receptor was described in the context of SGC in up to 50% of the cases, and most originated in the parotid gland (Tarakji & Kujan 2011; Nasser et al 2003). Its prevalence was distributed evenly between genders (Nasser et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that 16% (31/199) of the tumors were positive for AR expression, of which 61% (19/31) exhibited a strong expression [67]. Tarakji et al reported AR expression in 50% of the cases of pleomorphic salivary adenoma by immunohistochemical nuclear staining [68]. Additionally, the high expression of AR is associated with oncogenesis.…”
Section: Effects Of Ar On the Biological Behavior Of Hncmentioning
confidence: 97%